Clinicopathological characteristics of patients who underwent additional gastrectomy after incomplete endoscopic resection for early gastric cancer. Issue 7 (February 2017) - Hwang, Jae Jin; Lee, Dong Ho; Yoon, Hyuk; Shin, Cheol Min; Park, Young Soo; Kim, Nayoung
Abstract : Abstract: To evaluate the clinicopathological characteristics and factors that lead to residual tumors in patients who underwent additional gastrectomy for incomplete endoscopic resection (ER) for early gastric cancer (EGC). Between 2003 and 2013, the medical records of patients underwent additional gastrectomy after incomplete ER were retrospectively reviewed. Those diagnosed with the presence of histologic residual tumor in specimens obtained by gastrectomy were assigned to the residual tumor (RT) group (n = 47); those diagnosed with the absence of histologic residual tumor were assigned to the nonresidual tumor (NRT) group (n = 33). In the multivariate analysis, endoscopic piecemeal resection, Helicobacter pylori infection, large tumor size (>2 cm), and both (lateral and vertical) marginal involvement were independent factors of the presence of residual tumor in additional gastrectomy after incomplete resection ER for EGC and the rates of independent factors were significantly higher in the RT group than in the NRT group ( P < 0.05). Before ER, preexamination to accurately determine the GC invasion depth and the presence of LN metastasis is very important. During ER, surgeons should attempt to perform en bloc resection and to resect the mucous membrane with adequate safety margins to prevent tumor invasion into the lateral and vertical margins.